Tanggung Jawab Komisi Informasi Dalam Pembinaan Pejabat Pengelola Informasi Dan Dokumentasi Dalam Sengketa Informasi Publik - Mahendrayana, Indra Ashoka; Junaidi, Muhammad; Manurung, Mangaraja; Sudarmanto, Kukuh (Universitas Semarang, 2024)
The aim of this research is to analyze the responsibilities/authority of the Central Java Provincial Information Commission and its obstacles in developing Information and Documentation Management Officers (PPID) in resolving public information disputes. The type of research used in this writing is sociological legal research (sociolegal research) with a conceptual approach. Data analysis was carried out qualitatively. The Central Java Provincial Information Commission (KIP Central Java) has broad authority in developing Information and Documentation Management Officials (PPID) in its region which includes establishing information service standards, criteria and procedures for establishing PPID, as well as preparing technical guidelines. KIP also has a role in coaching through training, evaluation and supervision of PPID. In addition, KIP has the authority to handle complaints related to violations of the right to public information and can provide recommendations or sanctions. Monitoring, supervision and administrative actions are also part of KIP's responsibility to ensure PPID's compliance with legal provisions. The development of Information and Documentation Management Officers (PPID) by the Central Java Province Information Commission faces several obstacles, namely, regulations regarding the rights, authority and obligations of the Information Commission through the Council of Commissioners have not been clearly regulated in statutory regulations. In the Adjudication hearing there were also obstacles related to the Respondent's power of attorney, not all of whom were PPID. Then, PPID has difficulty ensuring the classification of the information requested by the Applicant, especially if the information is not listed as exempt information, and a lack of clear understanding of standard operational procedures can hinder the effective processing of information requests. Tujuan penelitian ini yaitu untuk menganalisis tanggung jawab/wewenang Komisi Informasi Provinsi Jawa Tengah dan kendalanya dalam pembinaan Pejabat Pengelola Informasi dan Dokumentasi (PPID) dalam penyelesaian sengketa informasi publik. Jenis penelitian yang digunakan dalam penulisan ini yakni penelitian hukum yuridis sosiologis (sociolegal research) dengan pendekatan konseptual. Analisa data dilakukan secara kualitatif. Komisi Informasi Provinsi Jawa Tengah (KIP Jawa Tengah) memiliki wewenang yang luas dalam pembinaan Pejabat Pengelola Informasi dan Dokumentasi (PPID) di wilayahnya yang mencakup penetapan standar pelayanan informasi, kriteria dan prosedur pembentukan PPID, serta penyusunan pedoman teknis. KIP juga memiliki peran dalam pembinaan melalui pelatihan, evaluasi, dan supervisi terhadap PPID. Selain itu, KIP memiliki kewenangan dalam menangani pengaduan terkait pelanggaran hak atas informasi publik dan dapat memberikan rekomendasi atau sanksi. Pemantauan, pengawasan, dan tindakan administratif juga menjadi bagian dari tanggung jawab KIP untuk memastikan ketaatan PPID terhadap ketentuan hukum. Pembinaan Pejabat Pengelola Informasi dan Dokumentasi (PPID) oleh Komisi Informasi Provinsi Jawa Tengah menghadapi beberapa kendala yakni, regulasi mengenai hak, wewenang, dan kewajiban Komisi Informasi melalui Majelis Komisioner belum diatur dengan jelas dalam peraturan perundang-undangan. Dalam sidang Ajudikasi juga terdapat kendala terkait kuasa Termohon yang tidak seluruhnya merupakan PPID. Lalu, PPID kesulitan memastikan klasifikasi informasi yang diminta oleh Pemohon, terutama jika informasi tersebut tidak terdaftar sebagai informasi yang dikecualikan, dan pemahaman kurang jelas terhadap prosedur operasional standar dapat menghambat pemrosesan permohonan informasi secara efektif.